2012
DOI: 10.1186/1471-2415-12-10
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study of VEGF induced changes in vasoactivity in pig retinal arterioles and the influence of an anti-VEGF agent

Abstract: BackgroundVascular endothelial growth factor (VEGF) plays an important role in ocular physiology. Anti-VEGF agents are now used for treatment of common retinal diseases. This study characterises the vasoactive properties of VEGF in isolated perfused pig retinal arterioles under normal tone or endothelin-1 (ET-1) pre-contracted conditions and determines the influence of an anti VEGF agent on VEGF induced vasoactivity.MethodsAn isolated perfused retinal arteriole preparation was used. The outer diameter of retin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
0
6
1
Order By: Relevance
“…Here, the number of anti-VEGF injections was not significantly correlated with the diameter of the occluded vein in the BRVO eye (Table 3). VEGF has a vasodilatory effect, and previous reports have suggested that anti-VEGF can be used to suppress the vasodilatory effect and reduce the permeability of the blood vessel [19]. However, in the current study, there was no significant correlation between the number of anti-VEGF injections and vessel diameter, suggesting that anti-VEGF treatment does not suppress vasodilation over long periods.…”
Section: Discussioncontrasting
confidence: 91%
“…Here, the number of anti-VEGF injections was not significantly correlated with the diameter of the occluded vein in the BRVO eye (Table 3). VEGF has a vasodilatory effect, and previous reports have suggested that anti-VEGF can be used to suppress the vasodilatory effect and reduce the permeability of the blood vessel [19]. However, in the current study, there was no significant correlation between the number of anti-VEGF injections and vessel diameter, suggesting that anti-VEGF treatment does not suppress vasodilation over long periods.…”
Section: Discussioncontrasting
confidence: 91%
“…It is conceivable that if VEGF serves to regulate vascular tone (Bardal et al, 2006) or BBB integrity, a chronic deficiency in VEGF signaling in the diabetic hippocampus could lead to an increase in the number of dilated vessels. This idea is supported by a recent study where local application of VEGF led to constriction of isolated retinal arterioles (Su et al, 2012). Alternatively, since diabetes has been linked to changes in cerebral perfusion in some reports (Harik and LaManna, 1988;Knudsen et al, 1991;Manschot et al, 2003;Wu et al, 2008) but not others (Jakobsen et al, 1990), vessel dilation could be a compensatory mechanism for maintaining sufficient blood flow to meet the high metabolic demands of the hippocampus (Stranahan and Mattson, 2008).…”
Section: Discussionmentioning
confidence: 91%
“…Direct administration of VEGF has been shown to induce vasorelaxation and lower BP (Henry et al, 2003; 2001; Horowitz et al, 1997). Bevacizumab inhibited VEGF-induced vasodilation, measured by outer vessel diameter, in pig retinal arterioles (Su, Cringle, McAllister, & Yu, 2012), and local administration of bevacizumab in human subjects rapidly decreased endothelium-dependent vasodilation (Thijs et al, 2013). Thus, inhibition of VEGF signaling and decreased endothelium-dependent vasodilation may result in overall vascular resistance and the development of HTN.…”
Section: Pathophysiological Mechanismsmentioning
confidence: 99%